2020
DOI: 10.4018/978-1-7998-2019-2.ch004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the National System of Social Security Over Senior Entrepreneurs

Abstract: The aim of this chapter is to analyze the relationship between the national systems of social security and senior entrepreneurial activity. To understand the growing phenomenon of senior entrepreneurship, the authors developed a multilevel model using a dataset from the Global Entrepreneurship Monitor that allows them to relate country-level variables, such as social security contributions, level of economic development, government support and policies, and burden taxes and bureaucracy, with individual-level v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Entrepreneurial activity is an engine of growth and should be encouraged (Acs et al , 2009; Acs and Stough, 2008; Lazear, 2005; Morris et al , 2013; Palma-Ruiz et al , 2020; Villegas Mateos and Amorós, 2020). The emergence of new ventures raises competition levels, reinforce diversity to the demand side, create job opportunities and increase tax revenue, providing general improvement in income generation (Storey, 1994).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Entrepreneurial activity is an engine of growth and should be encouraged (Acs et al , 2009; Acs and Stough, 2008; Lazear, 2005; Morris et al , 2013; Palma-Ruiz et al , 2020; Villegas Mateos and Amorós, 2020). The emergence of new ventures raises competition levels, reinforce diversity to the demand side, create job opportunities and increase tax revenue, providing general improvement in income generation (Storey, 1994).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Besides, in the last three years, there has been a 37% growth in publications relating to senior entrepreneurship. In this ebullition of studies, seminal and contemporary research is revealed, addressing aspects such as retirement and age for work (Dollinger et al , 1988), entrepreneurship as a second career (Baucus and Human, 1995; Ratten, 2019), the role of the elderly in society and self-employment (Curran and Blackburn, 2001; Figueiredo and Paiva, 2019), the effect of age on entrepreneurial behaviour (Lévesque and Minniti, 2006; Amorós et al , 2019; Weber and Schaper, 2004), along with comparisons between entrepreneurship in the third and first ages (Hart et al , 2004; Kautonen, 2008; Rehak et al , 2017; Villegas Mateos and Amorós, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a second objective, we analyze whether individual drivers for being a technology entrepreneur differ between senior and non-senior entrepreneurs. In doing so, this paper contributes to a better understanding of the best conditions for enhancing seniors' entrepreneurial initiatives given that empirical research on this issue is still scarce (Villegas Mateos & Amor os, 2020).…”
mentioning
confidence: 99%